Closing the gap in cardiomyopathy classification: A case report of the emerging non-dilated left ventricular phenotype - Sekarsari, Calysta Citra; Handari, Saskia Dyah (Universitas Brawijaya, 2026)
Background: In the latest ESC guidelines on cardiomyopathy management, the task force introduced several new concepts and recommendations, including a novel phenotype-based classification for cardiomyopathies, which refered Non-Dilated Left Ventricular Cardiomyopathy (NDLVC). This case underscores the critical importance of long-term follow up and adherence to the patient pathway approach, as emphasized in recently published clinical guidelines. Case Presentations: A young male patient was taken to the emergency room after he experienced a syncopal episode. An electrocardiogram (ECG) was performed, revealing multiple Premature Ventricular Contractions (PVC). Transthoracic echocardiography performed at the referral hospital revealed reduced systolic function, with a left ventricular ejection fraction (LVEF) of 37% and CT Angiography showed non-significant stenosis. A contrast-enhanced cardiac MRI was conducted, which identified hypokinesia and impaired systolic function. Neither fibrosis, sign of myocarditis nor other inflammatory diseases was detected. Based on these findings, a diagnosis of non dilated left ventricular cardiomyopathy is established. Importantly, despite the absence of a family history, genetic testing is needed to provide valuable insights for confirming the diagnosis and optimizing patient management through continuous monitoring and individualized treatment adjustments. Conclusions: In this case of a young patient with findings consistent with NDLVC, we highlight the importance of a cardiomyopathy-focused approach. This approach supports the selection of appropriate diagnostic tests, including genetic evaluation, to facilitate accurate risk stratification and phenotype-specific management.